Spatial Heterogeneity of Plant‐Level CCUS Investment Decisions in China's Cement Industry Under Various Policy Incentives - Yifan Mao; Kai Li; Jizhe Li; Xian Zhang; Jing‐Li Fan (Earth's Future)
Abstract Carbon Capture, Utilization, and Storage (CCUS) is widely regarded as a critical technology for achieving deep decarbonization in the cement industry. However, limited research has focused on its plant‐level CCUS investment decisions, especially considering geographic heterogeneity based on the national source‐sink matching optimization. This study develops an integrated framework that combines source‐sink matching with a real option model to investigate CCUS investment decisions under various incentive policies. The findings show that the critical carbon price varies significantly across regions in China, ranging from 55 to 950 CNY/t, with 297 (46% of retrofittable cement plants) falling between 600 and 800 CNY/t. Northeast China, benefiting from favorable storage conditions and enhanced oil recovery, exhibits a lower average critical carbon price of 104 CNY/t. In contrast, Central China, despite its substantial CO2 storage amount (18% of the national total), encounters a higher average critical carbon price of 564 CNY/t CO2 due to significant source‐sink matching distances. Notably, the offshore saline aquifer storage in the Southeastern coast could account for 17% of the national total, corresponding to an average critical carbon price of 660 CNY/t. Furthermore, implementing different policy incentives can enhance the immediate adoption of CCUS from 93 to 294 (13% to 46% of retrofittable cement plants).